1991
DOI: 10.1007/bf00190392
|View full text |Cite
|
Sign up to set email alerts
|

The control of vortex shedding behind heated circular cylinders at low Reynolds numbers

Abstract: We report some experiments undertaken to investigate the control of vortex shedding behind electrically heated cylinders at low Reynolds numbers owing to the heat input brought to the cylinder. In airflow, depending on the Reynolds number value, complete suppression or modification of the vortex shedding phenomenon can be achieved with increase of heat input. Experimental results suggest that this control could result of a slight change of the separation point location due to the increase of the dynamic viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(45 citation statements)
references
References 18 publications
3
39
0
1
Order By: Relevance
“…When the cylinder is exposed to a horizontal cross flow, Lecordier et al 9 and Wang et al 10 observed that for a Reynolds number just above the critical value of Re c ϭ49 the vortex shedding could be suppressed by a small amount of heat input to the cylinder in air. Heating the wake flow has an opposite effect in air and water, due to the difference in the thermal dependence of the kinematic viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…When the cylinder is exposed to a horizontal cross flow, Lecordier et al 9 and Wang et al 10 observed that for a Reynolds number just above the critical value of Re c ϭ49 the vortex shedding could be suppressed by a small amount of heat input to the cylinder in air. Heating the wake flow has an opposite effect in air and water, due to the difference in the thermal dependence of the kinematic viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…An original construction of the effective Reynolds number assumes that critical effective Reynolds numbers are the same for both unheated and heated cases [14,15,11]. However, the present T eff calculation could not use this approach.…”
Section: Effective Temperature and St-re Eff Relationshipmentioning
confidence: 93%
“…The idea of effective temperature was proposed originally by Lecordier et al [14], and used later by Dumouchel et al [15], who worked out this concept and calculated the effective kinematic viscosity m eff from an effective temperature T eff that is defined by…”
Section: Thermal Effects In Air and Water For Forced Convectionmentioning
confidence: 99%
“…For a horizontal mounted cylinder, the vortex shedding can be suppressed by heating of the cylinder at Reynolds values just above the critical value: Re c =49 ͑Lecordier et al, 5 Wang et al 6 ͒. In Lecordier et al, 7 the sudden disappearance of the vortex shedding phenomenon is analyzed and it is concluded that the influence of the temperature on the viscosity is the primary source.…”
Section: Introductionmentioning
confidence: 99%